Sleep quality and mental health among medical students in Imphal, Manipur: A cross-sectional study - Jalina Laishram; Sandra Fernandez; Pangambam A. Devi; Mani R. Bhowmick; Roshnee Heigrujam; Hanjabam S. Devi (Journal of Family Medicine and Primary Care)
Background: Sleep and mental health are deeply interlinked, with poor sleep quality, a common issue among medical students, having a profound impact on their mental well-being. Methods: A cross-sectional study was conducted among medical students in a tertiary care hospital in Imphal, Manipur. Data were collected using a self-administered questionnaire consisting of the Pittsburgh Sleep Quality Index (PSQI) and Depression Anxiety Stress Scale (DASS-21). Descriptive statistics, Chi-square test, and Pearson correlation test were applied, and P < 0.05 was considered statistically significant. Results: A total of 425 respondents took part in the study, including 268 undergraduate and 157 postgraduate students. Most participants, 236 (55.5%) had poor sleep quality. Among the participants, 168 (39.5%) had depression, 167 (39.3%) had anxiety, and 95 (22.4%) had stress. Poor sleep quality was significantly associated with academic year among undergraduate students (P = 0.005), increased total screentime per day (P = 0.024), and increased screentime before sleep (P = 0.007). Depression, anxiety, and stress were significantly associated with younger age (P = 0.001), the undergraduate course being pursued (P = 0.001, 0.003, and 0.001), and increased screen time before sleep (P = 0.021, 0.046, and 0.039). Depression, anxiety and stress scores had a significant positive correlation with the global PSQI score. Conclusion: More than half of the participants experienced poor sleep quality, with four out of ten experiencing depression or anxiety, and two out of ten experiencing stress. Hence, medical institutes must implement sleep hygiene education and screen time reduction initiatives to enhance students’ sleep quality and overall well-being.